Underlying drivers of deforestation in the Peruvian amazon and the highland region of the Andes - Juarez, H.; Pradel, W.; Navarrete, C.; Gutiérrez, D.; Hualla, V.; Vanegas, M.; Sylvester, J.; Castro, A. (2024)
Deforestation in Peru's Amazon and Andean regions is a critical environmental challenge with extensive economic, social, and ecological implications. The Amazon, known for its unparalleled biodiversity, has experienced the loss of approximately 100,000 hectares of forest over 34 years, primarily driven by small-scale agricultural practices and artisanal mining. In the Andean region, the imperative to reconcile rural development with environmental conservation has resulted in land-use practices that fail to meet sustainability criteria. This study examines the underlying drivers of deforestation in the Peruvian Amazon and Andean region during the 2000–2020 period, highlighting the importance of understanding how climatic, economic, landscape, and demographic influences interact with regional dynamics to shape deforestation patterns. The methodology integrates spatial analysis and advanced statistical modeling, leveraging a dataset encompassing demographic, climatic, economic, and ecological predictors. Results reveal that in the Amazon, the aggregation index (25.7%), population dynamics (21.9%), and temperature (16%) were key drivers of deforestation, with agricultural expansion and landscape fragmentation playing prominent roles. Conversely, in the Andes, rainfall (41.3%) and temperature (20.1%) constituted the predominant factors, whilst the incorporation of proximate causes, such as agricultural land use, enhanced the explanatory capacity of models across both regions. Furthermore, the aggregation index demonstrated heterogeneous impacts, with higher fragmentation facilitating deforestation in some districts while reducing it in others. Spatiotemporal analyses highlighted persistent and emerging deforestation hot spots, notably in Madre de Dios and San Martín, which corresponded to distinct drivers such as mining and agriculture. These findings underscore the necessity of tailored conservation policies and interventions that address the specific socio-economic and ecological contexts of the Amazon and Andes.